Teachers' attitudes and beliefs regarding education in virtual environments. Casos Universidad Pontificia Bolivariana and Universidad de Antioquia - López Vélez, Beatriz Elena (Íkala, Revista de Lenguaje y Cultura, 2005)
The article presents the results of the research process directed by the Virtual Environment Group (EVA). It describes opinions and attitudes of higher education - University - professors in regards to virtual environments. It is supported by 48 interviews conducted to professors of three areas of knowledge: basic science; applied science; and social and human science. Received: 10-05-05/ Accepted: 04-08-05 How to reference this article: López Vélez, B. L. (2005). Actitudes de los Docentes en relación con la Educación en Ambientes Virtuales. Casos: Universidad Pontificia Bolivariana y Universidad de Antioquia. Íkala. 10(1), pp. 171 – 193.